2004
DOI: 10.1177/1099800404263288
|View full text |Cite
|
Sign up to set email alerts
|

Are there Sex Differences in Emotional and Biological Responses in Spousal Caregivers of Patients with Alzheimer’s Disease?

Abstract: The purpose of this study was to compare emotional and biological responses of men and women who are spousal caregivers of patients with Alzheimer's disease (AD). Quality-of-life measurements, bioinstrumentation data, and immunophenotype assessments were obtained from female and male spousal caregivers of patients with AD. Spousal caregivers (women, n = 45 with average age 69.7; men, n = 16 with average age 71.4 years) completed questionnaires that assessed psychosocial variables. Blood was drawn and lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 66 publications
8
85
1
1
Order By: Relevance
“…'Emotional distress' was strongly related to a high level of BPSD, the hours spent caring per week and the carer being a female. This accords well with previous research showing that female carers are more prone to express distress, depression and anxiety due to their care obligations than males (Morris et al, 1991;Almberg et al, 1998;Gallicchio et al, 1998;Thompson et al, 2004;Bedard et al, 2005). Men and women differ in their ways of coping.…”
Section: Discussionsupporting
confidence: 92%
“…'Emotional distress' was strongly related to a high level of BPSD, the hours spent caring per week and the carer being a female. This accords well with previous research showing that female carers are more prone to express distress, depression and anxiety due to their care obligations than males (Morris et al, 1991;Almberg et al, 1998;Gallicchio et al, 1998;Thompson et al, 2004;Bedard et al, 2005). Men and women differ in their ways of coping.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, older people are more likely to present with comorbidity and therefore have an increased need for intensive care and support that may pave the way towards caregiver distress and burden (Papastavrou et al, 2009). Confirming existing findings (Hagedoorn et al, 2008;Papastavrou et al, 2009;Pinquart and S€ orensen, 2006;Thompson et al, 2004), female carers in this study perceived their role as more burdensome than male caregivers, which might have been underpinned by social expectations 'demanding' that the female members of families devote their selves to the care of the ill person. Carers of lower socioeconomic status and with less educational attainment were also found with greater burden (Clark, 2002); low education levels may be associated with low socio-economic levels and therefore with fewer available resources to meet caring demands.…”
Section: Discussionsupporting
confidence: 78%
“…Research here shows that men seem to adapt better than women to the caregiving situation (Gilhooly, Sweeting, Whittick, & McKee, 1994). In fact, Thompson et al (2004) demonstrated key differences in biological and emotional responses in spousal dementia caregivers: Male caregivers had significantly lower levels of stress, depression, anxiety, subjective caregiver burden, anger-hostility, and somatic symptoms as well as higher levels of social and physical functioning, mental health, and sense of coherence compared with female caregivers. No gender differences were found in social support and coping resources.…”
Section: Studies Focusing On the Caregiver's Perspectivementioning
confidence: 94%